EMT‐associated microRNAs and their roles in cancer stemness and drug resistance - Pan, Guangtao; Liu, Yuhan; Shang, Luorui; Zhou, Fangyuan; Yang, Shenglan (Cancer communications (London, England), 2021)
Epithelial‐to‐mesenchymal transition (EMT) is implicated in a wide array of malignant behaviors of cancers, including proliferation, invasion, and metastasis. Most notably, previou studies have indicated that both cancer stem‐like properties and drug resistance were associated with EMT. Furthermore, microRNAs (miRNAs) play a pivotal role in the regulation of EMT phenotype, as a result, some miRNAs impact cancer stemness and drug resistance. Therefore, understanding the relationship between EMT‐associated miRNAs and cancer stemness/drug resistance is beneficial to both basic research and clinical treatment. In this review, we preliminarily looked into the various roles that the EMT‐associated miRNAs play in the stem‐like nature of malignant cells. Then, we reviewed the interaction between EMT‐associated miRNAs and the drug‐resistant complex signaling pathways of multiple cancers including lung cancer, gastric cancer, gynecologic cancer, breast cancer, liver cancer, colorectal cancer, pancreatic cancer, esophageal cancer, and nasopharyngeal cancer. We finally discussed the relationship between EMT, cancer stemness, and drug resistance, as well as looked forward to the potential applications of miRNA therapy for malignant tumors. In this review, we preliminarily looked into the various roles that the EMT‐associated miRNAs play in the stem‐like nature of malignant cells. Then we reviewed the interaction between drug resistance and EMT‐associated miRNAs with elaborated signal pathways, especially the opposite roles in various cancer types. We finally arrived at a conclusion concerning the relationship between EMT, stemness and drug resistance and discussed the potential application of miRNA therapy for malignant tumors.